2021
DOI: 10.22456/1679-9216.116285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition Palmitic Acid and Vitamin E to the Tris-Egg Yolk Diluter in Canine Semen Cryopreservation

Abstract: Background: Canine sperm is a very delicate cell that is quite susceptible to oxidative stress since the cytoplasm is restricted and features little antioxidant reserves. Furthermore, the sperm membrane has some polyunsaturated fatty acids sensitive to lipid peroxidation, which makes it important to addition antioxidant substances to the diluter aiming at decreasing such stress to the sperm cell, particularly during seminal cryopreservation. Several antioxidants have been used in this process in some domestic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Excess fatty acids in human sperm may contribute to oxidative stress that is associated with male infertility, but stearic acid does not produce reactive oxygen species (ROS) (Aitken et al, 2006). Saturated fatty acids, stearic acids, palmitic, lignoceric, lauric and myristic acids failed to stimulate acrosome reaction in sperm of wild boars and hamsters (Hossain et al, 2007; Meizel & Turner, 1983) but studies showed that supplementation of TRIS‐Gema with 100 μM palmitic acid helped to preserve the membrane integrity of cryopreserved canine sperm (Sousa Filho et al, 2021). Palmitic acid can be synthesized from stearic acid, as shown in Figure 8a.…”
Section: Discussionmentioning
confidence: 99%
“…Excess fatty acids in human sperm may contribute to oxidative stress that is associated with male infertility, but stearic acid does not produce reactive oxygen species (ROS) (Aitken et al, 2006). Saturated fatty acids, stearic acids, palmitic, lignoceric, lauric and myristic acids failed to stimulate acrosome reaction in sperm of wild boars and hamsters (Hossain et al, 2007; Meizel & Turner, 1983) but studies showed that supplementation of TRIS‐Gema with 100 μM palmitic acid helped to preserve the membrane integrity of cryopreserved canine sperm (Sousa Filho et al, 2021). Palmitic acid can be synthesized from stearic acid, as shown in Figure 8a.…”
Section: Discussionmentioning
confidence: 99%